MATEC Web of Conferences - Gaydabrus, M. (EDP Sciences, 2018)
As a result of the functioning of the agro-industrial complex, several million tons of bran that require recycling are annually produced in Russia. At present, there is no resource-efficient way of utilizing bran, which ensures its ecological compatibility and economic efficiency. In this regard, the purpose of the paper is to investigate the possibility of using wheat bran as a building material. The article presents the prerequisites for the construction of low-rise buildings using wheat bran as a building material: an experiment was carried out for the manufacture of bran blocks, and their thermophysical characteristics, maximum crushing strength, and moisture resistance were measured. Building blocks made from bran have a thermal conductivity comparable to the thermal conductivity of wood. The high strength of the bran blocks to squeeze indicates the possibility of their use for the construction of low-rise buildings without any strengthening of their design. However, this blocks exhibit hydrophilic properties, which requires the application of a protective layer. For example, a conventional wood varnish can be use as such a coating.